“Real-life” continuous flash suppression (CFS)-CFS with real-world objects using augmented reality goggles - Korisky, Uri (Behav Res Methods, 2018)
Continuous flash suppression (CFS) is a popular method for suppressing visual stimuli from awareness for relatively long periods. Thus far, this method has only been used for suppressing two-dimensional images presented on screen. We present a novel variant of CFS, termed “real-life” CFS, in which a portion of the actual immediate surroundings of an observer—including three-dimensional, real-life objects—can be rendered unconscious. Our method uses augmented reality goggles to present subjects with CFS masks to the dominant eye, leaving the nondominant eye exposed to the real world. In three experiments we demonstrated that real objects can indeed be suppressed from awareness for several seconds, on average, and that the suppression duration is comparable to that obtained using classic, on-screen CFS. As supplementary information, we further provide an example of experimental code that can be modified for future studies. This technique opens the way to new questions in the study of consciousness and its functions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.3758/s13428-018-1162-0) contains supplementary material, which is available to authorized users.